Croatian Chemistry in the 20th Century. IV.: Croatian Chemical Journals - Raos, N.; Bazdar-Pausek, S.; Trinajstic, N.; Skare, D. (Kemija u industriji; časopis kemičara i tehnologa Jugoslavije, 2008)
The beginnings and the developments of the main Croatian chemical journals that are referred to in the number of international information sources are presented. These are the Croatica Chemica Acta, published by the Croatian Chemical Society and the Kemija u industriji (Chemistry and Industry) and Chemical and Biochemical Engineering Quartely, published by the Croatian Society of Chemical Engineers and Technologists. Also stressed is the important role that the first short-lived Croatian chemical journal Revue Chimique had in the development of Croatian chemical publishing.All editors of the three main Croatian chemical journals are listed and in the case of the Croatica Chemica Acta, all titles that this journal carried from its beginning in 1927. Additionally, the journals Priroda (Nature) and Prirodoslovlje (Natural Sciences) that publish articles from all fields ofnatural sciences including chemistry, are mentioned since they are important in the popularization of science in Croatia. Priroda is the oldest Croatian natural-science journal - the first issue appeared on July 3, 1911. Prirodoslovlje publishes articles about the development of Croatian science and Croatian scientific achievements through history. However, chemistry articles in both journals are relatively few.